موافقات الشيخ الألباني لحكم السيوطي على أحاديث الجامع الصغير من حديث 401 - 410: Al-Albānī’s Concurrences with al-Suyūṭī’s Rulings on the Ḥadīths in al-Jāmiʿ al-Ṣaghīr: A Study of Ḥadīths 401 - 410 - Forat Mustafa Almazloum,; Kabiru Goje, (Maʿālim al-Qurʾān wa al-Sunnah, 2024)
This study addresses the discrepancy between the symbolic notations employed by al-Ḥāfiẓ al-Suyūṭī in his rulings on selected hadith and the interpretations subsequently provided by Shaykh al-Albānī. Specifically, it examines hadith numbers 401 to 410 found in al-Suyūṭī’s al-Jāmiʿ al-Ṣaghīr fī Aḥādīth al-Bashīr al-Nadhīr, with the aim of identifying instances where al-Albānī’s assessments align with Al-Suyūṭī’s judgments. Methodologically, the research adopts an inductive approach to analyse the chosen hadith, followed by a comparative examination of their symbolic evaluations as presented in al-Jāmiʿ al-Ṣaghīr and in al-Albānī’s two works, Ḍaʿīf al-Jāmiʿ al-Ṣaghīr wa Ziyādatuhu and Ṣaḥīḥ al-Jāmiʿ al-Ṣaghīr wa Ziyādatuhu. The findings reveal that al-Albānī’s rulings concur with al-Suyūṭī’s in eight of the ten examined hadith, diverging in only two instances. In light of these results, the study encourages scholarly institutions to undertake a comprehensive comparative analysis of all remaining hadith in al-Jāmiʿ al-Ṣaghīr, thereby advancing the precision and reliability of future evaluations.